2021
DOI: 10.3390/healthcare9101353
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Monitoring the Reasons for Hesitation with COVID-19 Vaccine Based on Social-Platform Text and Classification Algorithms

Abstract: (1) Background: The COVID-19 pandemic is globally rampant, and it is the common goal of all countries to eliminate hesitation in taking the COVID-19 vaccine and achieve herd immunity as soon as possible. However, people are generally more hesitant about the COVID-19 vaccine than about other conventional vaccines, and exploring the specific reasons for hesitation with the COVID-19 vaccine is crucial. (2) Methods: this paper selected text data from a social platform to conduct qualitative analysis of the text to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…1 not only subdivides the hesitant and resistant types into four types but also structures them according to the two dimensions of agency and health capital. When compared to a typology of 12 COVID-19 vaccine hesitancy reasons ( Liu et al, 2021 ), the four ideal types proposed in this article are based on more general underlying mechanisms, each of which can be assumed to be driven by one or more of these 12 reasons. Underlying diseases, the possibility of adverse reactions, pregnancy and lactation, fear of needles, and allergies, for example, might to some degree contribute to the mechanism of personal fear.…”
Section: Resultsmentioning
confidence: 99%
“…1 not only subdivides the hesitant and resistant types into four types but also structures them according to the two dimensions of agency and health capital. When compared to a typology of 12 COVID-19 vaccine hesitancy reasons ( Liu et al, 2021 ), the four ideal types proposed in this article are based on more general underlying mechanisms, each of which can be assumed to be driven by one or more of these 12 reasons. Underlying diseases, the possibility of adverse reactions, pregnancy and lactation, fear of needles, and allergies, for example, might to some degree contribute to the mechanism of personal fear.…”
Section: Resultsmentioning
confidence: 99%
“…A character-level short text classification model based on BERT, a Robustly Optimized BERT Pretraining Approach (RoBERTa), XLNet, and ERNIE was proposed for eligibility criteria text classification, and they use the focal loss as a loss function to solve the problem of data imbalance among different categories [ 35 ]. SMOTE has also been commonly used in some studies to solve the problem of data imbalance by oversampling some minority classes [ 36 ]. The above methods brought us insights to solve the problem of data imbalance in the subsequent multicategory study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the automatic-identification model of reasons for COVID-19 vaccine hesitation and the twelve types of COVID-19 vaccine hesitation reasons model developed in previous studies, we classified the valid posts [79], in which 12,703 posts were, respectively, identified as one of the twelve types of vaccine-hesitation reasons. After classification, the distribution of the number of valid posts among the twelve types of COVID-19 vaccine hesitation reason is shown in Figure 1.…”
Section: Data Collectionmentioning
confidence: 99%